Integrated analysis of mRNA and microRNA expression profiles in hepatopancreas of Litopenaeus vannamei under acute exposure to MC-LR - Zhang, Dajuan; Huang, Lanying; Jia, Yingxuan; Zhang, Shulin; Bi, Xiandong; Dai, Wei (Frontiers in Genetics, 2023)
Intensive shrimp farming is often threatened by microcystins (MCs). Hepatopancreas is the primary target organ of MCs in shrimp. To investigate the response of hepatopancreas to acute MC-LR exposure, the expression profiles of RNA-seq and miRNA-seq in the hepatopancreas of L. vannamei were determined, and data integration analysis was performed at 72 h after MC-LR injection. The expression of 5 DEGs and 3 DEMs were detected by Quantitative PCR (qPCR). The results showed that the cumulative mortality rate of shrimp in MC-LR treatment group was 41.1%. A total of 1229 differentially expressed genes (DEGs) (844 up- and 385 down-regulated) and 86 differentially expressed miRNAs (DEMs) (40 up- and 46 down-regulated) were identified after MC-LR exposure. Functional analysis indicated that DEGs is mainly involved in the oxidative activity process in molecular functional categories, and proteasome was the most enriched KEGG pathway for mRNAs profile. According to the functional annotation of target genes of DEMs, protein binding was the most important term in the GO category, and protein processing in endoplasmic reticulum (ER) was the most enriched KEGG pathway. The regulatory network of miRNAs and DEGs involved in the pathway related to protein degradation in ER was constructed, and miR-181-5p regulated many genes in this pathway. The results of qPCR showed that there were significant differences in the expression of 5 DEGs and 3 dem, which might play an important role in the toxicity and hepatopancreas detoxification of MC-LR in shrimp. The results revealed that MC-LR exposure affected the degradation pathway of misfolded protein in ER of L. vannamei hepatopancreas, and miR-181-5p might play an important role in the effect of MC-LR on the degradation pathway of misfolded protein.